Tunes that move us: the impact of music-induced emotions on prosocial decision-making - Hongwei Wu; Danni Wang; Linshu Zhou (Frontiers in Psychology)
IntroductionThe significance of music might be attributed to its role in social bonding, a function that has likely influenced the evolution of human musicality. Although there is substantial evidence for the relationship between prosocial songs and prosocial behavior, it remains unclear whether music alone, independent of lyrics, can influence prosocial behaviors. This study investigates whether music and the emotions it induces can influence prosocial decision-making, utilizing the classical two-dimensional model of emotion (mood and arousal).MethodsIn Experiment 1,42 undergraduate students listened to happy music (positive, high arousal), sad music (negative, low arousal), and white noise while reading stories describing helping scenarios and then assessed their willingness to help. Experiments 2 and 3 further explore mood and arousal effects by manipulating the mode (major vs. minor) and tempo (fast vs. slow) of the music.ResultsExperiment 1’s results indicated that sad music increases willingness to help more than happy music or white noise, suggesting that music-induced emotions influence prosocial behavior through immediate prosocial emotions like empathy. Experiments 2 and 3 demonstrated that only mood, influenced by the music mode, affects prosocial decision-making, while tempo-induced arousal does not. Additionally, Theory of Mind and memory strength do not mediate these effects.DiscussionThese findings reveal the role of pure music listening and specific emotional dimensions on prosocial decision-making, providing evidence to support the music-social bonding hypothesis.